Penerimaan Diri Individu Yang Memiliki Pasangan Dengan Pekerjaan Sebagai Pemandu Karaoke Di Desa Sarirejo, Salatiga - Meylani, Risda; Desi, Desi; Suwartiningsih, Sri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Â This study aims to determine the couple's self-acceptance from the karaoke guide to the karaoke guide itself.Methods: The research method used is descriptive qualitative with five participants. This research was conducted in January - April 202.1 Results: Â The results showed that there was self-acceptance of the karaoke guide couple as a whole as a form of relationship commitment. Self-acceptance is found in the positive behavior of karaoke guide couples who accept anything without it.Conclusion: Â The acceptance starts from knowledge and a positive attitude towards their partner. The karaoke guide couple has known the impact or risk of their relationship but still chooses a karaoke guide to be their life partner.Keywords: Ladies Companion, Partner, Self-Acceptance